2016
DOI: 10.1681/asn.2015101155
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Receptor–Related Membranous Nephropathy and Mannan-Binding Lectin Deficiency

Abstract: Most patients with idiopathic membranous nephropathy (IMN) have IgG4 autoantibodies against phospholipase A2 receptor (PLA2R). C3 and C5b-9 are found in immune deposits of IMN kidney biopsy specimens, but the pathway of complement activation in IMN remains elusive. We report the case of a patient who developed IMN with intense staining for PLA2R, IgG4, C3, C5b-9, factor B, and properdin and very weak staining for C1q, C4d, and IgG1. Measurement of mannan binding lectin (MBL) antigenic level and activity reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 35 publications
(40 reference statements)
3
75
1
3
Order By: Relevance
“…In a study comparing 21 membranous patients with 19 patients with minimal change disease (MCD), capillary C4d deposition (via IHC) was present in 100% of membranous patients and in none of the MCD patients [37]. Bally et al [38] report a case of IMN in a patient with deficiency of MBL in whom complement activation was thought to occur via AP activation; they further evaluated 77 patients with idiopathic MN, and found similar MBL deficiency in 4 patients in whom there was weak C4d staining. However, all remaining patients with intact MBL had intense C4d staining (via IF) along glomerular capillary wall indicating activation via LP.…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…In a study comparing 21 membranous patients with 19 patients with minimal change disease (MCD), capillary C4d deposition (via IHC) was present in 100% of membranous patients and in none of the MCD patients [37]. Bally et al [38] report a case of IMN in a patient with deficiency of MBL in whom complement activation was thought to occur via AP activation; they further evaluated 77 patients with idiopathic MN, and found similar MBL deficiency in 4 patients in whom there was weak C4d staining. However, all remaining patients with intact MBL had intense C4d staining (via IF) along glomerular capillary wall indicating activation via LP.…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…Although immune complexes mainly activate complement via the classical pathway, glomerular deposition of factor B and properdin also occurs in membranous nephropathy [108, 109], lupus nephritis [110], and anti-GBM antibody disease [111], indicative of the alternative pathway activation. These findings suggest insufficient complement regulation by factor H, which may be exacerbated by the loss of GBM heparan sulfate, as depicted in Figure 3.…”
Section: The Role Of Gbm Heparan Sulfate Chains In Local Complemenmentioning
confidence: 99%
“…In the present study, genotype O/O, previously related to a 2.6-fold greater risk of developing LN [20], was not encountered in any of the patients. Only Bally et al [21] have evaluated the presence of MBL2 polymorphism in IMN. The authors reported that 5 out of 78 patients presented genotypes associated with low serum levels of MBL; however, there was no comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that IMN occurs in genetically susceptible individuals; however, very few studies have investigated the possible relationship between this glomerulopathy and polymorphisms of the MBL2 gene, which is responsible for producing MBL [15][16][17][18]. Although lupus nephritis is associated with genetic variants of MBL2 and the consequent deficient production of the MBL protein [19,20], only Bally et al [21] have evaluated the sequencing of the MBL2 gene in IMN, and found polymorphisms in 5 out of 78 patients. This gene is responsible for producing the amino acid sequences of the collagen triple helix of the MBL2 [22].…”
Section: Introductionmentioning
confidence: 99%